Relation between Serum Homocysteine level and Esophageal Varices in Cirrhotic Patients - Mohammed Mousa Abd Elhammed Elshenawy, Medhat A Ghazy, Nahla A Nosair, Tamer haydara (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Liver disease accounts for approximately two million deaths per year worldwide, one million due to complications of liver cirrhosis (LC). Aim: This study aims to assess relation between the level of serum Homocysteine and esophageal varices in cirrhotic patients and if can be used as a marker for predicting esophageal varices in cirrhotic patients. Methods: This prospective study was carried out on 90 patients with established liver cirrhosis based upon clinical, laboratory and ultrasonographic findings in Faculty of Medicine Kafr Elsheikh University. They were divided into 2 groups; Group (A) Included 45 cirrhotic patients with Esophageal varices based on GI endoscopy and Group (B): Included 45 cirrhotic patients without Esophageal varices. Results: The optimal cut-off value for homocysteine identified in this analysis was 23.483 µmol/L, achieving both high sensitivity and specificity (93.33% for each). This level of accuracy suggests that homocysteine is an excellent biomarker for identifying patients with and without esophageal varices. Conclusion: The study conclusively demonstrates that serum homocysteine levels are significantly elevated in cirrhotic patients with esophageal varices compared to those without, making it a reliable predictive marker for the presence of varices